ANALISIS MINAT BELI ONLINE PADA SHOPEE (STUDI PADA MAHASISWA PENGGUNA SHOPEE DI KOTA BANDAR LAMPUNG) - Orariri, Cindy Angelica (Jurnal Kompetitif Bisnis, 2020)
This study was aimed to find out the effect of perceived of risk, website quality, and customer trust in online purchase intetion of Shopee users students in Bandar Lampung. This type of explanatory research with a quantitative approach. The population in this study were students from various universities in Bandar Lampung. The data was obtained from a questionnaire filled out online, the sampling technique used purposive sampling with a total sample of 100 people. Data analysis in this study used multiple linear regression analysis with SPSS 25.0 computer software tools. Based on the results of research and data analysis shows that perceived of risk, website quality, customer trust simultaneously effect online purchase intetion. While the partial test results of each variable showed that perceived of risk significantly affected online purchase intetion, website quality significantly affected online buying interest, and customer trust significantly affected online purchase intention.